2013
DOI: 10.32674/jis.v3i2.504
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Advisors’ Experiences with International Graduate Students

Abstract: The current study explored the experiences of faculty advisors working with international graduate students (IGS). Data was collected through semi-structured interviews and a demographic survey and was analyzed using open, axial, and selective coding strategies. Three central categories emerged from the analysis: (a) advisors’ perceptions of IGS, (b) lessons learned by advisors, and (c) indicators of success. A model for advisors’ experiences emerged using the data gathered. Overall, advisors reported positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Trahar (2014) has observed that there is an unwillingness of these three local ethnic groups to associate with other ethnic groups, and this reluctance may "complicate" integration between Malaysian and international students. On the other hand, international students also have a tendency to befriend students from similar countries because they come from the same culture, speak the same language (Nguyen 2013), or have previously studied in similar systems and therefore share various experiences.…”
Section: Resilience In Group Assignmentsmentioning
confidence: 99%
“…Trahar (2014) has observed that there is an unwillingness of these three local ethnic groups to associate with other ethnic groups, and this reluctance may "complicate" integration between Malaysian and international students. On the other hand, international students also have a tendency to befriend students from similar countries because they come from the same culture, speak the same language (Nguyen 2013), or have previously studied in similar systems and therefore share various experiences.…”
Section: Resilience In Group Assignmentsmentioning
confidence: 99%
“…Although supervision is a complex process, because both parties have converging and diverging interests concurrently, balancing these interests (Baydarova et al, 2021) is necessary for a sustainable relationship. Supervisors in Nguyen's (2013) study said that keeping long-term contact with students also meant collaborating on research projects and writing papers together, even though students may have graduated ten years earlier.…”
Section: Further Research Collaboration Relationshipsmentioning
confidence: 99%
“…International students have also reported communication issues with their supervisors (González-Ocampo and Castelló, 2018): international students tend to think in their native language first before translating their research-related ideas into English, and this can cause misinterpretation of information communicated to their supervisors. An American-based study by Nguyen (2013) finds that postgraduate international students from Asian countries have language proficiency-related challenges, and this has negative impact on their thesis or assignment writing ability.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…International student-supervisor conflicts have been found to result from international students' lack of English proficiency, unclear expectations, lack of openness, time, and feedback (Adrian-Taylor, Noels, & Tischler, 2007). However, the advisors know that international students are hardworking (Nguyen, 2013). Research has found that host nation students generally seek help from their supervisors only on academic or vocational problems but turn to friends or other sources for help on emotional and other personal problems (Leong & Sedlacek, 1986).…”
mentioning
confidence: 99%